Pariwisata Spiritual di Bali - Made Budiasih (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
Spiritual tourism is a new phenomena in tourism industry. New age is one of the groups which raises an idea of spiritual journey, because they promoted a spirituality without border. The idea open the opportunities for the spirituality from different etnic for becoming a spiritual destination. Bali is one of destination spiritual tourism, but the Bali government havenot serious yet to take over its all. Therefore, it needed efforts to organize Bali as the spiritual destination.